Age of riverine carbon suggests rapid export of terrestrial primary production in tropics. Issue 21 (8th November 2013) - Martin, Erin E.; Ingalls, Anitra E.; Richey, Jeffrey E.; Keil, Richard G.; Santos, Guaciara M.; Truxal, Laura T.; Alin, Simone R.; Druffel, Ellen R. M.
Abstract [1] The balance between the storage of vascular plant carbon in soils, oxidation to carbon dioxide, and export via rivers affects calculations of the strength of terrestrial ecosystems as carbon sinks. The magnitude and timescale of the riverine export pathway are not well constrained. Here we use radiocarbon dating of lignin phenols to show that plant‐derived carbon carried by suspended sediment of the Mekong River is very young, having been produced within the last 18 years. Further, this plant‐derived carbon remains young during times of the year when bulk carbon varies from modern to over 3000 radiocarbon years old. Our results demonstrate that primary‐production derivatives are exported rapidly and suggest that the age of riverine lignin is similar to estimates of the residence time of terrestrial organic carbon in tropical catchments. These results are relevant for modeling predictions of the influence of the terrestrial biosphere on atmospheric carbon dioxide levels.